ASSOCIATIONS BETWEEN EARLY MATERNAL DEPRESSIVE SYMPTOM TRAJECTORIES AND TODDLERS' FELT SECURITY AT 18 MONTHS: ARE BOYS AND GIRLS AT DIFFERENTIAL RISK?. Issue 1 (2nd January 2017) - Beeghly, Marjorie; Partridge, Ty; Tronick, Ed; Muzik, Maria; Rahimian Mashhadi, Mahya; Boeve, Jordan L.; Irwin, Jessica L.
ABSTRACT: The goal of this study was to evaluate whether there are sex differences in children's vulnerability to caregiving risk, as indexed by trajectories of maternal depressive symptoms assessed from 2 to 18 months' postpartum, and children's rated attachment security in toddlerhood, adjusting for maternal social support and demographic risk. Analyses utilized longitudinal data collected for 182 African American mother–child dyads from economically diverse backgrounds. Participants were recruited at the time of the child's birth and followed to 18 months' postpartum. Results of conditional latent growth models indicated that an increasing rate of change in level of maternal depressive symptoms over time negatively predicted toddlers' felt attachment security. Higher social support was associated with decreasing levels of maternal depressive symptoms over time whereas higher demographic risk was associated with increasing levels of maternal depressive symptoms. A subsequent multigroup conditional latent growth model revealed that child sex moderated these associations. For male (but not female) children, a rapid increase in maternal depressive symptoms was associated with lower felt attachment security at 18 months. These findings suggest that boys, as compared to girls, may be more vulnerable to early caregiving risks such as maternal depression, with negative consequences for mother–child attachment security in toddlerhood.